The Relation of Moodle-Based Self-Regulated Learning With Grade 11 Students’ Metacognitive Skills : [Hubungan Self-Regulated Learning Berbasis Moodle dengan Keterampilan Metakognitif Siswa Kelas 11] - Sipromia Dethan; Kevvin Kevvin; Levana Vivian Nurtanto (Universitas Pelita Harapan, 2023)
This research investigates the relation between Moodle based self-regulated learning and Metacognitive skills of grade 11 students in XYZ High School Tangerang, within the context of online asynchronous Applied Mathematics course. The research sample contained 105 students enrolled in this course. Researchers employed quantitative methods, collected data through survey questionnaires and analyzed it using correlation and linear regression methodologies. The results revealed a strong correlation (Pearson Correlation value = .619) between Moodle-based self-regulated learning and grade 11 students’ metacognitive skills in online asynchronous Applied Mathematics course in XYZ High School. The linear regression analysis indicated that Moodle-based self-regulated learning has a significant contribution towards students’ metacognitive skills as represented by the linear equation Y = 46.647 + 0.414X. This research makes an important contribution by how Moodle-based self-regulated learning can enhance students’ metacognitive skills in the context of online asynchronous Applied Mathematics course.